The Integration of Artificial Intelligence as a Teacher’s Partner in Islamic Religious Education Learning - Nun, Luluk Ilma'; Mohtarom, Ali; Marzuki, Ahmad; Lawal, Uthman Shehu (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
The rapid advancement of AI has transformed various sectors, including education. In Islamic Religious Education (Pendidikan Agama Islam / PAI), AI has the potential to enhance effectiveness and inclusiveness through personalized learning, task automation, and active interaction. However, challenges such as low digital literacy, limited infrastructure, and ethical issues remain obstacles. This study aims to examine the role of AI as a teacher’s partner in Islamic Religious Education and to analyze its opportunities and challenges. Using a qualitative approach, this research employs a literature review method by analyzing previous studies and relevant sources on AI implementation in education, particularly in the PAI context. The findings indicate that AI can support teachers by automating assessments, providing adaptive learning content, and facilitating immersive learning experiences through virtual and augmented reality. However, effective implementation requires digital literacy training for educators, improved infrastructure, and the development of ethical policies. These findings highlight the need for collaboration among governments, educational institutions, and technology developers to ensure AI integration aligns with Islamic values and enhances both cognitive and character development in students.